HAK ASUH ANAK DIBAWAH UMUR MENURUT ADAT LEWA DiKABUPATEN SUMBA TIMUR (STUDI KASUS DI DESA KONDAMARA KECAMATAN LEWA KABUPATEN SUMBA TIMUR) - Laos, Gerald Yustenlye Khamtry; Hedewata, Agustinus; Mauritsius, Darius (Petitum Law Journal, 2023)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the Almighty Godhead. In marriage, a man and woman form a bond that leads to the formation of an ideal family with the goal of living together forever. This research uses empirical juridical legal research methods, carried out by collecting data consisting of interviews, direct data collection from the research location, and document study. The data collected was processed and analyzed using qualitative research methods. Based on the research results, it can be concluded that, (1) Factors inhibiting the distribution of child custody. Marriage factors in society are very influential in terms of the distribution of child custody rights, and cultural factors. (2) The process of dividing child custody is not solely based on who has the most rights, but what must be seen and prioritized is the best interests of the child.